2023
DOI: 10.1002/adfm.202212891
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Covalent Organic Framework as a Positive Tribo‐Material for High‐Performance Triboelectric Nanogenerators

Abstract: Along with the increasingly wide application of intelligent electronics, triboelectric nanogenerator (TENG), as a promising sustainable micro-power source has attracted considerable attention recently. However, most of the reported research focuses on negative triboelectric materials, while research on alternative positive tribo-layers is still limited. In this study, a new highly fluorinated covalent organic framework (COF) Tp-TFAB is successfully synthesized and utilized as positive triboelectric materials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…139 A novel fluorinated COF based on 1,3,5-tris(2,3,5,6-tetrafluoroaniline) benzene (TFAB) and triformylphloroglucinol (Tp) is combined with PVA to form a positive tribo-layer for high performance TENGs. 140 Furthermore, a cationic TFP-DB-COF based on the 1,3,5-triformylphloroglucinol (TFP) knot and dimidium bromide (DB) linker is proposed, with cationic groups exposed to the channel surface (Fig. 6b).…”
Section: Covalent Organic Framework (Cofs) As Triboelectric Polymersmentioning
confidence: 99%
“…139 A novel fluorinated COF based on 1,3,5-tris(2,3,5,6-tetrafluoroaniline) benzene (TFAB) and triformylphloroglucinol (Tp) is combined with PVA to form a positive tribo-layer for high performance TENGs. 140 Furthermore, a cationic TFP-DB-COF based on the 1,3,5-triformylphloroglucinol (TFP) knot and dimidium bromide (DB) linker is proposed, with cationic groups exposed to the channel surface (Fig. 6b).…”
Section: Covalent Organic Framework (Cofs) As Triboelectric Polymersmentioning
confidence: 99%
“…For example, Lin Shi et al reported the synthesis of a highly fluorinated COF, Tp-TFAB COF, for use as a positive electrode material. [93] This COF was synthesized using 1,3,5-tris(2,3,5,6-tetrafluoroaniline)benzene (TFAB) and triformylphloroglucinol (Tp). The synthesis of Tp-TFAB and Tp-TAPB COFs involved the solvothermal method (shown in Figure 3g).…”
Section: Crystalline Porous Structured Materials Synthesis: Peng and ...mentioning
confidence: 99%
“…Very few studies are reported on COF-based TENGs in the literature. [90][91][92][93][94][95] The first demonstration of TENG using COFs was reported in 2020 and used TPB-DBBA-COF with monomer 2,5-dibromobenzene-1,4-dicarbaldehyde (DBBA) as linker and 1,3,5-tris (4-aminophenyl) benzene (TPB) as knot used with bromine functionalization. [90] In this report, COFs are functionalized with an electron-withdrawing bromine group onto the skeletons of COFs.…”
Section: Cofs-based Tengsmentioning
confidence: 99%
See 2 more Smart Citations